The impact of physical exercise on university students’ life satisfaction: The chain mediation effects of general self-efficacy and health literacy - Yu-Peng Ye; Guo-You Qin; Xinyu Zhang; Shan-shan Han; Bo Li; Ning Zhou; Qi Liu; Chen-Xi Li; Yang-sheng Zhang; Qian-qian Shao (PLoS ONE, 2025)
Objective This study aims to explore the impact of physical exercise on university students’ life satisfaction and analyses the chain mediation effect of general self-efficacy and health literacy, providing empirical reference and theoretical foundation for the comprehensive enhancement and optimization of students’ mental health. Method Based on data from the “China University Student Physical Activity and Health Tracking Survey” (CPAHLS-CS) 2024, the measurement scales used included the Physical Activity Rating Scale (PARS-3), the Satisfaction with Life Scale (SWLS), the General Self-Efficacy Scale (GSES), and the 9-item Short Form Health Literacy Scale (HLS-SF9). A total of 4575 valid samples were analyzed. Results A significant positive correlation was found between physical exercise and life satisfaction (r = 0.137, P < 0.01). The total effect of physical exercise on university students’ life satisfaction was significant, with an effect value of 0.045 (95%CI = [0.035, 0.054]). The chain mediation effect of general self-efficacy and health literacy in the relationship between physical exercise and life satisfaction was significant, with an effect value of 0.005 (95%CI = [0.004, 0.006]), accounting for 11.4% of the total effect. The direct effect of physical exercise on life satisfaction had a standardized regression coefficient of 0.001, which was not significant. Conclusion University students’ life satisfaction is closely related to physical exercise, general self-efficacy, and health literacy. General self-efficacy and health literacy play a full mediating role in the effect of physical exercise on life satisfaction.